Hubungan Kebersihan Lingkungan dan Kelembapan Udara Dengan Kejadian Kusta di Kabupaten Jeneponto - S, Sapriadi; Wanci, Risman; Syahridha, Syahridha (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Objective: to analyse the relationship between environmental hygiene and humidity with the incidence of leprosy in Jeneponto District.Methods: This research used observational descriptive research with Case Control approach. Data collection techniques are carried out by survey and observation. Sampling was taken by purposive sampling for case samples and control samples. Case samples were lepers in Jeneponto district. And the control sample were non-lepers sample in Jeneponto district. Researchers matched the type of house between cases and controlsResults: The results of the study by Chi square statistical test showed that there was a significant relationship between environmental hygiene with the incidence of leprosy( p value = 0.002 <0.05) and there was a significant relationship between humidity with the incidence of leprosy ( p = 0.022 <0.05).Conclusion: Leprosy is an infectious disease that has a predictive factor of leprosy caused by environmental hygiene and humidity